CRITERIA FOR ASSESSING THE STABILITY OF INFORMATION SYSTEMS OF CRITICAL INFRASTRUCTURE FACILITIES - Zhaksygulova Д.; Rakhmetullina С.Ж.; Gnatyuk С.А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The article considers the problems and approaches to assessing the resilience of information systems (IS), especially in the context of critical infrastructure facilities (CI). The first section discusses the theoretical foundations of IS resilience, including definitions and key concepts such as fault tolerance, adaptability, and a systems approach. The second section provides an overview of existing resilience assessment methods such as risk analysis, stress testing, modeling, and simulation, and their applicability to CI. The third section analyzes the identified problems, including insufficient integration of methods, limited forecasting capabilities, insufficient adaptability of systems, and difficulties in managing interdependencies. Based on the systems approach, resilience assessment criteria are proposed that include integration of methods, system adaptability, dependency analysis, use of dynamic forecasting models, and implementation of incident response plans. The article emphasizes the importance of an integrated approach to resilience assessment and suggests directions for further research and practical application of the developed methods and criteria.